Combined pathway-based biomarker discovery and ESR2 gene, polymorphism analysis of litter size prediction in sheep using a, multi model bioinformatics toolbox - Javanmard, Arash; Yazdanyar, Mansour; Ebrahimi, Mahdi; Rafat, Abbas; Hasanpur, Karim; Panahi, Babak Ghasemi; Alijani, Sadegh; Cheraghi, Habib; Sheikhlou, Mohammadreza; Mohammadabadi, Mohammadreza; Esmailizadeh, Ali (Elsevier, 2026)
By utilizing a comprehensive multi-modal approach that combined in silico modeling, in vitro molecular assays, in vivo microscopic observations, and on-farm phenotyping, we aimed to improve comprehension of the genetic architecture related to sheep litter size (LS). Our goal was to assess a T/C polymorphism (rs423810437) in the ovine Estrogen Receptor 2 (ESR2) gene and find potential LS biomarkers by applying network and circuit analysis. The sequencing of this polymorphism involved four populations, specifically the Romanov, Ghezel, Lori Bakhtiari, and their crossbreeds. With strong support for BMPR1B, GDF9, and ESR2, our analysis found more than ten candidate genes linked to LS. In purebred Romanov and Romanov-crossbred sheep, the ESR2 C allele was significantly correlated (p < 0.01) with increased LS. As our research suggests, the ESR2 polymorphism, among the identified candidate genes, is a valuable biomarker for litter size, offering understanding of follicular development in prolific sheep.